Design and Applications of Electronically Tunable Floating Resistor Using Differential Amplifier - Tekin, S. A.; Alçı, M. (Elektronika ir Elektrotechnika, 2013)
In this paper, a new electronically tunable active resistance was introduced. The proposed circuit design consists of only two differential amplifiers. The main advantages of this circuit are higher bandwidth, simpler design and tunable resistance range. Also, the design of the circuit allows negative resistance structure and besides it can be used in IC realizations. Effective range of the floating resistor is controlled within a wide range of resistance in between ± 43 Ω – ± 516 kΩ. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1310